Supramolecular polyelectrolyte complexes based on cyclodextrin-grafted chitosan and carrageenan for controlled drug release. (1st October 2020) - Evangelista, Thamasia F.S.; Andrade, George R.S.; Nascimento, Keyte N.S.; dos Santos, Samuel B.; de Fátima Costa Santos, Maria; Da Ros Montes D'Oca, Caroline; dos S. Estevam, Charles; Gimenez, Iara F.; Almeida, Luís E.
Graphical abstract: Highlights: Supramolecular polyelectrolyte complex between βCD-CS and CRG were prepared. Silver sulfadiazine was incorporated to the polyelectrolyte complex. The contact between silver sulfadiazine and βCD-CS/CRG produces silver nanostructures. Semiempirical molecular modeling studies suggest the host/guest complex formation. βCD-CS/CRG-SSD showed a clean antibacterial activity toward various bacterial strains. Abstract: In the present study, supramolecular polyelectrolyte complexes (SPEC) based on a cyclodextrin-grafted chitosan derivative and carrageenan were prepared and evaluated for controlled drug release. Samples were characterized by FTIR, SEM, and ζ-potential measurements, which confirmed the formation of the polymeric complex. The phenolphthalein test confirmed the presence and availability of inclusion sites from the attached βCD. Silver sulfadiazine was used as the model drug and the association with the SPEC was studied by FTIR and computational molecular modeling, using a semi-empirical method. DRS and TEM analyses have shown that Ag + ions from the drug were reduced to form metallic silver nanostructures. In vitro tests have shown a clear bacterial activity toward Gram-positive bacteria Staphylococcus aureus and Enterococcus durans/hirae and Gram-negative bacteria Klebsiella pneumoniae and Escherichia coli . Finally, this work shows that βCD-chitosan/carrageenan supramolecular polyelectrolyte complexes hold an expressive potential to be applied as a polymer-based system for controlled drug release.